A helyi gazdaságfejlesztés aspektusai Fertőd példáján - Péter, Orsolya (Jelenkori Társadalmi és Gazdasági Folyamatok, 2014)
We often do not even know what potentials our regions have, and optionally how unique they are appropriate. Seeking after the competitiveness of regions every region must find its own unique competitive factor or the main sector of the local economy. The main sector of Fertöd's economy may be the tourism based on the famous Esterházy Palace, the music scene and the natural factors. Recommended further strengthening and more effective using of these attractions. It may be important to create and propagate an overall image of Fertőd, in which the cultural and natural values distinguish the town from others. This may be the city's message to the outside world, which is important to become an inner motivation of the residents as well.